Forging a Legacy through Intergenerational Learning in Family Businesses: A Bibliometric Exploration - Oktiwanti, Lesi; Kamil, Mustofa; Hufad, Achmad; Shantini, Yanti (KnE Social Sciences, 2024)
Intergenerational learning plays a crucial role in family businesses, facilitating knowledge transfer and business skills across generations. This study conducted a bibliometric analysis of intergenerational learning research trends in the family business context from 2013 to 2023. The analysis utilized the VOSviewer application to map the research landscape and identify key themes. In the past 10 years, research on intergenerational learning in family businesses has been comparatively rare, with only 116 publications, or 10 per year on average. The highest number of citations occurred in 2013, 2015, and 2017, with China leading in Asian studies. Social sciences, medicine, and psychology were the prominent disciplines in this field. The analysis revealed clusters of key terms such as child, father, intergenerational, parent, research, digital divide, older adult, perspective, family, intergenerational transmission, language, role, and violence. The study also identified less-explored areas within intergenerational learning, including older adults, children, and the digital divide. Indonesia’s focus on family education and cultural heritage transmission could advance research in this field. Overall, this study contributes to the comprehension of forging a legacy through intergenerational learning in the context of family businesses and establishes a foundation for future research directions. Keywords: bibliometric, family business, intergenerational learning, legacy